PENGARUH PROFIL RISIKO TERHADAP VARIABEL FINANCIAL DISTRESS (STUDI KASUS PADA BANK KBMI 1 – 4 SERTA BANK BUMN DAN BUSN PERIODE 2017-2021) - Mohammad Irham Muqoddam; Sakti, Rachmad Kresna (Contemporary Studies in Economic, Finance and Banking, 2024)
This study aimed to analyze the bank's health assessment instrument through the risk profile of the RBBR component with bankruptcy prediction using the Bankometer model. This study used the category of Banks Based on Core Capital (KBMI) class 1 to 4 for the period 2017 to 2021. The components in this study include several risk profiles of a bank including Loan to Deposit Ratio, Non Performance Loans, BOPO, Return on Assets, Capital Adequacy Ratio and Inflation, while Bankometer is measured using the S-Score. The results of the study stated that the risk profile that significantly affects the research sample is credit risk and liquidity, it can be concluded that the higher the capital determined by the bank in order to continue to gain investor confidence but cannot manage properly, it will only increase the high burden on the bank's risk value.